Comportamiento epidemiológico de distribución espacial, temporal y condición climática de Leptospirosis de la provincia de El Oro, del periodo 2013 al 2022 - Espinoza Vásquez, Lorena del Cisne (2024)
Leptospirosis is a zoonotic disease caused by the bacterium Leptospira, with endemic potential and recognized as the most widespread zoonosis globally. It is considered a public health problem in countries where the sanitary standards are not consistently met, especially in tropical climates. For this reason, the following objective was proposed: to determine the epidemiological behavior, including spatial and temporal distribution, as well as leptospirosis climatic conditions in the province of El Oro from 2013 to 2022, with the aim of developing an educational proposal to reduce the prevalence of the disease. A retrospective, analytical, descriptive study with a mixed approach and crosssectional design was conducted to describe certain sociodemographic and meteorological patterns of leptospirosis cases. These cases were obtained from reports of the Ministry of Public Health from 2013 to 2022 through the Disease Surveillance System (SIVE-Alert by its Spanish acronym). Data on precipitation and temperature were collected from the National University of Loja database, and the data processing was carried out using the Statistics Package for the Social Sciences (SPSS). A total of 40 cases of leptospirosis were reported. The results showed a higher prevalence among men with 70%, in the 30 to 39-year-old age group with 60%, and in the Machala canton with 65%. Additionally, the rainy season was found to influence the incidence of cases, while temperature was not observed to have a significant effect. An audiovisual digital educational resource was developed, providing clear information and achieving broad spreading, with an emphasis on prevention. Finally, it is recommended that prospective studies be conducted, including the creation of predictive statistical models to contribute to the development of an early warning system focused on environment, animal health and human health